Delivering a research‐enabled multistakeholder partnership for enhanced patient care at a population level: The Northern Ireland Comprehensive Cancer Program. Issue 5 (22nd December 2015) - Lawler, Mark; Gavin, Anna; Salto‐Tellez, Manuel; Kennedy, Richard D.; Van Schaeybroeck, Sandra; Wilson, Richard H.; Harkin, Denis Paul; Grayson, Margaret; Boyd, Ruth E.; Hamilton, Peter W.; McArt, Darragh G.; James, Jacqueline; et al.
Abstract : The last 20 years have seen significant advances in cancer care in Northern Ireland, leading to measureable improvements in patient outcomes. Crucial to this transformation has been an ethos that recognizes the primacy role of research in effecting heath care change. The authors' model of a cross‐sectoral partnership that unites patients, scientists, health care professionals, hospital trusts, bioindustry, and government agencies can be truly transformative, empowering tripartite clinical‐academic‐industry efforts that have already yielded significant benefit and will continue to inform strategy and its implementation going forward.